PROBLEMS OF COMBINE COLLECTION OF POTATO ARE ON SOILS - Бончик, В. С.; Федірко, П. П.; Дудчак, Т. В.; Корчак, М. М. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
A hardware of technologies of collection of potato is on soils by the improvement of constructions of working organs of combine. Realization of researches came true with the use of substantive provisions of theoretical mechanics, statistics, probability and discipline theory from exploitation of park. Expediency of the use of methods of previous destruction of lumps is reasonable, and also the rational placing of working organs of combine offers. It offers to work out the structural chart of combine that would execute next technological operations: previous destruction of layer, separation to the lots, transporting bulbar in a transport vehicle, that simultaneously moves from the side of the collected field